ANALISIS TINGKAT KEPUASAN ANGGOTA TERHADAP KUALITAS PELAYANAN KARYAWAN CREDIT UNION KELING KUMANG KOTA PUTUSSIBAU - Novita, Sri; Jang, Paulinus (Business, Economics dan Entrepreneurship, 2024)
This research was conducted at the Keling Kumang Credit Union, Putussibau City, the reason for this research was to answer the author's curiosity regarding the level of satisfaction felt by members during the 15 years CUKK was founded. The aim is to determine the level of member satisfaction in the quality of service of Keling Kumang Credit Union employees, Putussibau City. In this research, the author uses indicators in the form of Tangibles, Reliability, Responsiveness, Assurance, Emphaty, and Service. The research method used is a descriptive method in the form of qualitative descriptive research. Data collection techniques include field observations, questionnaires and interviews. Based on the results of research conducted through indicators in Credit Union member service, namely Tangibles (Tangible), Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Guarantee), Emphaty (Empathy), and Service and placement of employees in the right positions and has a good relationship between the employees of the Keling Kumang Credit Union, Putussibau City and its members, with an average score of 2.88, which means that if you look at the dimensions and indicators with a range of interpretations, it can be concluded in the range 2.36 – 3.03 so it is in the category strongly agree or very well.